2011
DOI: 10.1371/journal.pone.0018588
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 by Nutlin-3a Induces Apoptosis and Cellular Senescence in Human Glioblastoma Multiforme

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor in adults. Despite concerted efforts to improve current therapies and develop novel clinical approaches, patient survival remains poor. As such, increasing attention has focused on developing new therapeutic strategies that specifically target the apoptotic pathway in order to improve treatment responses. Recently, nutlins, small-molecule antagonists of MDM2, have been developed to inhibit p53-MDM2 interaction and activate p53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 45 publications
21
110
0
Order By: Relevance
“…Nutlin-3a was the lead compound in the field 57 but few data addressed its effects in GBM. Here, we show that it activated p53-dependent transcription of pro-apoptotic targets but also repressed anti-apoptotic genes confirming other works 25 without inducing full apoptosis in glioma cells overexpressing the α5β1 integrin. Repression of anti-apoptotic/survival genes in addition with induction of pro-apoptotic targets was shown to critically control the apoptotic outcome of RITA-treated cancer cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nutlin-3a was the lead compound in the field 57 but few data addressed its effects in GBM. Here, we show that it activated p53-dependent transcription of pro-apoptotic targets but also repressed anti-apoptotic genes confirming other works 25 without inducing full apoptosis in glioma cells overexpressing the α5β1 integrin. Repression of anti-apoptotic/survival genes in addition with induction of pro-apoptotic targets was shown to critically control the apoptotic outcome of RITA-treated cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…Along with others, we demonstrated that p53-induced activation either by genotoxic drugs 24 or by inhibitors of HDM2 such as Nutlin-3a-triggered 25 senescence rather than apoptosis in GBM. We characterized a negative crosstalk between α5β1 integrin and p53wt implicated in temozolomide (TMZ) resistance.…”
supporting
confidence: 77%
“…The results suggested that upon single Nut3a and double Nut3a-CDDP treatment, cells overexpressing Survivin showed decreased apoptosis compared to cells expressing basal levels of Survivin, although the differences were not statistically significant, which is in accordance with the previously published data. 13,29 Thus, overexpression of Survivin would be unable by itself to abolish apoptosis completely in OVCa cells. Nevertheless, downregulation of Survivin still may play a role in apoptosis induction in concert with other changes induced by Nut3a.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
“…The induction of senescence by Nut3a has already been described by our group in the human glioblastoma multiforme model. 13 The double treatment caused cell lines enter into cell-cycle arrest in G2/M phase, and, in primary cell cultures, the persistent induction of p21 protein observed suggested that cellcycle arrest exceeded the duration of treatment. Arrested cells would go senescent (majority of primary cell cultures) or apoptotic (primary cell cultures and mainly cell lines), thus decreasing the growth of tumor cells.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation